COMMODIFICATION OF RELIGION: BETWEEN RELIGION AND MANIPULATION (A LITERATURE REVIEW) - Pujianto , Wahyu Eko; Yulianto, Mochamad Rizal; Hidayatulloh, Hidayatulloh (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Objective: This study investigates the current practices of religious commodification and their effects on religious authenticity, focusing on how commercialization impacts the spiritual integrity of religious values. Method: Employing a literature study approach, the research analyzed 53 articles selected from databases such as Google Scholar, ScienceDirect, ProQuest, JIM, and ResearchGate. These articles were drawn from an initial pool of 30,590 publications related to religious commodification, with 20 articles serving as the analytical framework. Results: The findings reveal that religious commodification is a manipulative practice aimed at material gain, often resulting in the erosion of spiritual values and the reduction of religion to a consumable commodity. This process undermines the sacredness of religious practices, transforming them into tools for societal and economic exploitation. Novelty: The study highlights that religious commodification is not merely a commercial phenomenon but a materialistic intrusion that challenges the foundational beliefs and authenticity of religious practices. This perspective underscores the need to reexamine the balance between spiritual and material elements in religious contexts. Future research should incorporate direct case studies to provide empirical insights into the nuanced practices of religious commodification, offering critical guidance for religious communities and policymakers